Hyperpolarised xenon production via Rb and Cs optical pumping applied to functional lung MRI - Newton, Hayley Louise (2014)
Hyperpolarisation encompasses a multitude of methods to increase the species' spin polarisation for nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) applications. Hyperpolarised 129Xe is produced via spin-exchange optical-pumping (SEOP). Firstly, electronic spins of alkali metal vapour are polarised via absorption of circularly polarised light. Alkali metal polarisation is subsequently transferred to noble gas nuclei via collisions. Within this thesis, the SEOP process is examined by probing the kinetics of the 129Xe polarisation build up. A combination of diagnostic techniques are used including low field NMR to measure 129Xe polarisation (PXe) at different spatial positions, near-IR optical absorption to give a global estimate of the alkali metal polarisation, and in situ Raman spectroscopy to spatially monitor the energy transport processes by detecting the internal gas temperatures (TN2). TN2 values were found to be dramatically elevated above oven thermocouple readings, with observations of up to 1000 K for an oven heated to only 400 K. Internal gas temperatures are presented for the first time along the length of the optical cell, showing spatial temperature and PXe variations during steady state and rubidium runaway conditions. Two contrasting methods of Raman spectroscopy are examined: a conventional orthogonal arrangement of detection and excitation optics, where intrinsic spatial filtering of the probe laser is utilised; and a newly designed inline module with all components in the same optical plane. Optical filtering is used to reduce the Rayleigh scattering and the probe laser line. This new inline device is presented herein and has a 23 fold improvement in signal to noise enabling increased accuracy and precision of `real-time' temperature monitoring. Rubidium, caesium and a rubidium/caesium hybrid are compared as the alkali metal of choice in the SEOP process. Caesium has a higher spin-exchange cross-section with 129Xe, thus a system is envisaged where current Rb D1 lasers in many polarisers can be utilised with a Rb/Cs hybrid to gain improvements in polarisation rates or levels. Xenon polarisations are shown up to 50% for a hybrid cell. Finally, preparatory experiments crucial to the imminent lung imaging study are presented, including measurements of PXe at low and high magnetic fields. In addition, polariser technology is examined including the current Nottingham device and an open-source consortium polariser.